ЛАПАРОСКОПСКА ТАПП НАСПРОТИ ПОПРАВКА ПО LICHTENSTEIN; РАН КЛИНИЧКИ ИСХОД - Mitevski, Aleksandar; Antovikj, Svetozar; Markov, Petar; Jankulovski, Nikola (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2020)
Introduction. Laparoscopy as a minimally invasive technique has itsplace in inguinal hernia repair. Lower postoperative pain, earlier mobilization and earlier return to usual activities are comparable to an initially high cost of the hospital charge. Also, there is a lower percentage of postoperative complications especially related to the wound. Methods. The study was designed as a prospective randomized controlled study conductedin a three-year-period. Sixty-five patients were randomly assigned into two groups, examined-35 patients treated with TAPP technique and controlled-30 patients treated with Lichtenstein technique. Surgicaltime, preoperative pain, hospital stay, postoperative analgesia, functional status and convalescence were evaluated. The postoperative complications, hematoma, seroma, wound infection and urinary retention were also taken into consideration. Results. A significant diference was found in the surgicaltime favoring Lichtenstein over TAPP technique; postoperative hospitalization was significanlly longer in case of the Lichtenstein procedure. There wasa significant difference concerning postoperative pain and functional status between the groups, as well as in the same group regarding the postoperative days. The percentage of early postoperative complications wassignificantly lower in TAPP group (6.3% versus 16.7%); there wasa significant difference in convalescence (TAPP 4.6±1.2 / Lichtenstein 6.6±1.10). Conclusion. Patients treated with laparoscopic TAPP technique had better early clinical outcome compared to open Lichtenstein technique. It is a result of a lower intensity of the postoperative pain, less postoperative complications which leads to a shorter hospital stay, better functional status and short convalescence.
LAPAROSCOPIC TAPP VERSUS LICHTENSTEIN REPAIR - ERLY CLINICAL OUTCOME
Keywords: inguinal hernia; laparoscopic hernia repair; open hernia repair; TAPP; early clinical outcome